Large-Capacity Three-Party Quantum Digital Secret Sharing Using Three Particular Matrices Coding*Supported by the Fundamental Research Funds for the Central Universities under Grant No. XDJK2016C043 and the Doctoral Program of Higher Education under Grant No. SWU115091, the National Natural Science Foundation of China under Grant No. 61303039, the Fundamental Research Funds for the Central Universities under Grant No. XDJK2015C153 and the Doctoral Program of Higher Education under Grant No. SWU114112, and the Financial Support the 1000-Plan of Chongqing by Southwest University under Grant No. SWU116007. (1st November 2016) - Lai 赖, Hong 红; Luo 罗, Ming-Xing 明星; Pieprzyk, Josef; Tao 陶, Li 丽; Liu 刘, Zhi-Ming 志明; Orgun, Mehmet A.
Abstract: In this paper, we develop a large-capacity quantum digital secret sharing (QDSS) scheme, combined the Fibonacci- and Lucas-valued orbital angular momentum (OAM) entanglement with the recursive Fibonacci and Lucas matrices. To be exact, Alice prepares pairs of photons in the Fibonacci- and Lucas-valued OAM entangled states, and then allocates them to two participants, say, Bob and Charlie, to establish the secret key. Moreover, the available Fibonacci and Lucas values from the matching entangled states are used as the seed for generating the Fibonacci and Lucas matrices. This is achieved because the entries of the Fibonacci and Lucas matrices are recursive. The secret key can only be obtained jointly by Bob and Charlie, who can further recover the secret. Its security is based on the facts that nonorthogonal states are indistinguishable, and Bob or Charlie detects a Fibonacci number, there is still a twofold uncertainty for Charlie' (Bob') detected value.